Transformasi Kompetensi Digital Guru Melalui Pelatihan Desain Perangkat Pembelajaran Berbasis AI: Studi Kasus Penggunaan Gamma AI Di SD IT Al-Qur’an Assakinah Medan - Samsiah Nur; Nur’azizah Bancin; Silvia Wati (TAUJIH: Jurnal Pendidikan Islam, 2025)
Artificial intelligence (AI) technology has opened up new opportunities for teachers to sharpen their digital competencies and adaptive in designing new learning experiences. This study aims to analyze the extent to which Gamma AI design training can enhance teachers' abilities in creating effective and creative learning designs, particularly in designing learning material presentations (PowerPoint). This study uses a qualitative method with a case study design. It was conducted at SD IT Al-Qur’an Assakinah Medan. Data were collected through participant observation, in-depth interviews, questionnaires, and document analysis of 15 participating teachers. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and drawing conclusions. The results of this study indicate that this training program has led to significant changes in teachers' technological abilities. The majority of participants experienced a clear improvement in their mastery of Gamma AI features, particularly related to creating interactive teaching materials and structuring engaging learning presentations, significantly contributing to three main dimensions of teacher competency transformation: technological skills, pedagogical creativity, and ethical-professional reflection. As many as 86.3% of teachers showed improved ability to operate AI applications to design interactive learning tools, while most participants also experienced increased reflective awareness of the ethics of AI use in the context of Islamic education. This training not only improved the efficiency and quality of learning design but also fostered a new paradigm of teachers as creative and reflective designers in the digital era.